TERT promoter mutation in primary papillary thyroid carcinoma lesions predicts absent or lower 131i uptake in metastases. Issue 7 (26th April 2019) - Meng, Zhaowei; Matsuse, Michiko; Saenko, Vladimir; Yamashita, Shunichi; Ren, Peng; Zheng, Xiangqian; Jia, Qiang; Tan, Jian; Li, Ning; Zheng, Wei; Zhao, Li; Mitsutake, Norisato
Abstract: Genetic mutations play important roles in not only development of papillary thyroid carcinoma (PTC) but also determination of its properties. The radioactive iodine refractory (RAIR) state is a harbinger of poor outcomes for PTC. We used various statistical models to investigate the significance of TERT promoter, BRAF, and RAS mutations in distinguishing the RAIR state and their associations with 131 I uptake. Mutations were examined in primary lesions of 33 RAIR cases and 34 age‐ and sex‐matched 131 I‐treated cases with disease‐free status. Thyrotropin‐stimulated thyroglobulin (sTg) change, 131 I uptake ability, and RAIR categories were evaluated in the RAIR cases. The prevalence of TERT mutation in the RAIR group was 24.24% (8/33), which was significantly higher than that in the disease‐free group (0/34). BRAF mutation showed a similar high prevalence in both the RAIR group (69.70%) and disease‐free group (64.71%). Among the eight TERT mutation‐positive cases, six carried both TERT and BRAF mutations. RAS mutation was detected in only one disease‐free case and in two RAIR cases. Despite a significantly higher prevalence of TERT mutations in the RAIR group, only tumor size and N1b lymph node involvement were independently associated with RAIR status. In the RAIR group, all patients carrying a TERT mutation showed maximum or increased sTg. Multivariate analyses demonstrated that the TERT mutation was associated with decreased 131 I uptake and the RAIR categories of absent or weaker 131 I uptake. TERT mutation constitutes a novel genetic biomarker indicating absent or weaker 131 I‐avid lesions in RAIR PTC patients. It is worth evaluating the TERT status in all DTC patients undergoing 131 I therapy. © 2019 IUBMB Life, 2019